BURNT FOOD CHAIN AN INTERDISCIPLINARY APPROACH IN THE AREA OF SCIENCE FOR ELEMENTARY EDUCATION - Krupek, Rogerio Antonio [UNESP]; Deon, Geize Aparecida; Froelich, Adriane [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2016)
This paper aims to present a proposal for interdisciplinary activity involving the disciplines of Sciences and Physical Education of Elementary Education. The theme is worked the food chain and the practical activity involves a dodgeball game on this topic. The game was organized to bring the students to understand the trophic chain through a dynamic and engaging way. The activities were applied to classes of 7th grade of elementary school in a college of the municipality of Uniao da Vitoria, Parana state. The results showed that the students had a very great interest in the activity, with remarkable initial difficulty, however, going to understand the game, and hence the process of transfer of matter/energy in the food chain.
Keywords: Food chain; Teaching science; Interdisciplinarity